LOCAL OPEN GOVERNMENT: STUDIES IN WEST NUSA TENGGARA, INDONESIA - Afandi, Syed Agung; Afandi, Muslim; Erdayani, Rizki (Jurnal Administrative Reform, 2023)
This research aims to analyze the bibliography and the local open government content of West Nusa Tenggara. This research uses a qualitative approach with bibliometric analysis and content analysis methods. This research uses secondary data obtained from the Google Scholar database and West Nusa Tenggara open government policy documents. The results of this research show that there are 160 publications, 376 citations, a 10 h-index, and a 15 g-index. However, the trend shows a decrease in publications every year. There are 149 keywords, 14 clusters, 3210 total link strengths, and 797 occurrences in the West Nusa Tenggara paper. Open government, local open government, NTB One Data, NTB Care, and Posyandu Information System are the dominant keywords. In implementing open government, the West Nusa Tenggara government implemented three policies: improving the West Nusa Tenggara One Data (NTB One Data) information system, improving the West Nusa Tenggara Care (NTB Care) information system, and revitalizing the Integrated Health Service Post (Posyandu). In their implementation, these policies encounter various challenges, but if they can be implemented, they will have the opportunity to provide quality public services in West Nusa Tenggara.